Physicochemical properties of endodontic sealers of different bases - Gabriela Alexandra Marín-Bauza; Yara Teresinha Correa Silva-Sousa; Suely Aparecida da Cunha; Fuad Jacob Abi Rached-Junior; Idomeo Bonetti-Filho; Manoel Damião Sousa-Neto; Carlos Eduardo Saraiva Miranda (University of São Paulo, 2012)
OBJECTIVE: To assess the setting time (ST), flow (FL), radiopacity (RD), solubility (SB) and dimensional change following setting (DC) of different sealers (AH Plus®, Polifil, Apexit Plus®, Sealapex®, Endométhasone® and Endofill®) according to American National Standards Institute/American Dental Association (ANSI/ADA) Specification 57. MATERIAL AND METHODS: Five samples of each material were used for each test. For ST, cast rings were filled with sealers and tested with a Gilmore needle. For FL, the sealer was placed on a glass plate. After 180 s, another plate with 20 g and a load of 100 g were applied on the material, and the diameters of the discs formed were measured. In RD, circular molds were filled with the sealers, radiographed and analyzed using Digora software. For SB, circular molds were filled with the sealers, a nylon thread was placed inside the material and another glass plate was positioned on the set, pressed and stored at 37°C. Samples were weighed, placed in water, dried and reweighed. The water used for SB was analyzed by atomic absorption spectrometry. For DC, circular molds were filled with the sealers, covered by glass plates and stored at 37°C. Samples were measured and stored in water for 30 days. After this period, they were dryed and measured again. RESULTS: Regarding ST, AH Plus®, Apexit® and Endofil® sealers are in accordance with ANSI/ADA standards. Endométhasone's manufacturer did not mention the ST; Polifil is an experimental sealer and Sealapex® did not set. Considering RD, SB and DC, all sealers were in accordance with ANSI/ADA. The spectrometric analysis showed that a significant amount of K+ and Zn2+ ions was released from Apexit Plus® and Endofill®, respectively. CONCLUSION: Except for DC, all other physicochemical properties of the tested sealers conformed to ANSI/ADA requirements.